Payments for Agrobiodiversity Conservation Services (PACS): Current status and implications for a re-introduction of colored Kiwicha (Amaranth) in Cusco, Peru - Drucker, Adam G.; Estrada, Erika; Ramírez, Marleni; Medina, Tulio (Bioversity International and the International Center for Tropical Agriculture, 2021)
Summary of a PACS intervention: Current status and implications for a re-introduction of colored Kiwicha (Amaranth) in Cusco, Peru